Paeoniflorin Derivative in Paeoniae Radix Aqueous Extract Suppresses Alpha-Toxin of Staphylococcus aureus - Liu, Xiaoye; Zhang, Yafei; Li, Zengshun; Zhang, Pengpeng; Sun, Ying-Jian; Wu, Yi-Jun (Frontiers in Microbiology, 2021)
The emergence and dissemination of bacterial infections is paralyzing our public health systems world widely. Worse still, there are no effective antibiotics against bacterial toxins, which facilitate the infection. Natural herbs that target bacterial toxins may be a better choose for therapy of infectious diseases. However, most natural drugs presented unknown compositions and unclear mechanisms. Here we demonstrated that the Chinese herb Paeoniae Radix aqueous extract (PRAE) could suppress alpha-toxin (α-toxin) of Staphylococcus aureus. We observed that the paeoniflorin derivative (PRAE-a) derivative in PRAE significantly abolished the hemolytic activity of S. aureus α-toxin. The analyses of high-performance liquid chromatography (HPLC), mass spectrometer (MS), Fourier transform infrared spectrometer (FTIR) and nuclear magnetic resonance (NMR) showed that PRAE-a was a glycoside compound with a paeoniflorin nucleus. We further found that PRAE-a disrupted the pore-forming ability of α-toxin by prevention of the dimer to heptamer. Therefore, PRAE-a were effective therapy on S. aureus lung infections in mice by inhibiting α-toxin. Collectively, these results highlighted the PRAE-a used as the antibacterial agent to attenuate S. aureus virulence by targeting α-toxin.